Unveiling the Cultivation of Nostoc sp. under Controlled Laboratory Conditions - Teresa Mouga; Jéssica Pereira; Vitória Moreira; Clélia Afonso (Biology, 2024)
Cyanobacteria, photoautotrophic Gram-negative bacteria, play a crucial role in aquatic and terrestrial environments, contributing significantly to fundamental ecological processes and displaying potential for various biotechnological applications. It is, therefore, critical to identify viable strains for aquaculture and establish accurate culture parameters to ensure an extensive biomass supply for biotechnology purposes. This study aims to establish optimal laboratory batch culture conditions for Nostoc 136, sourced from Alga2O, Coimbra, Portugal. Preliminary investigations were conducted to identify the optimal culture parameters and to perform biomass analysis, including protein and pigment content. The highest growth was achieved with an initial inoculum concentration of 1 g.L−1, using modified BG11 supplemented with nitrogen, resulting in a Specific Growth Rate (SGR) of 0.232 ± 0.017 μ.day−1. When exposed to white, red, and blue LED light, the most favourable growth occurred under a combination of white and red LED light exhibiting an SGR of 0.142 ± 0.020 μ.day−1. The protein content was determined to be 10.80 ± 2.09%. Regarding the pigments, phycocyanin reached a concentration of 200.29 ± 30.07 µg.mL−1, phycoerythrin 148.29 ± 26.74 µg.mL−1, and allophycocyanin 10.69 ± 6.07 µg.mL−1. This study underscores the influence of light and nutrient supplementation on the growth of the Nostoc biomass.